Shaving Rituals and Religious Identity in the Malay World: A Study of the Hikayat Nabi Bercukur - Ali, M. Nasihudin (IAIN Manado, 2025)
Abstract: This study aims to analyze the influence of the shaving ritual on the formation of the religious identity of the Malay community by referring to the text of the Hikayat Nabi Bercukur as the primary source. The shaving tradition in the Malay world not only functions as a social practice, but also contains spiritual values that strengthen the relationship between Islamic teachings and local customs. Using a quantitative-qualitative approach, this study tested several independent variables, namely exposure to the Hikayat Nabi Bercukur, the intensity of participation in the shaving ritual, and family norms and local traditions, against the dependent variable of the community's religious identity. The results show that the level of exposure to the Hikayat Nabi Bercukur and the intensity of involvement in the shaving ritual have a significant influence on the strengthening of individual and community religious identity. Meanwhile, family norms and cultural traditions play a role as reinforcing factors in maintaining the continuity of the practice amidst modernization and social change. These findings confirm that the shaving tradition is not merely a cultural heritage, but also a syncretic representation of Islamic values and the ethno-religious identity of the Malay community in the Indonesian archipelago. Key Words: The Story of the Prophet Shaving; Shaving tradition; Malay society; Religious identity; Cultural syncretism. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh ritual bercukur terhadap pembentukan identitas keagamaan masyarakat Melayu dengan merujuk pada teks Hikayat Nabi Bercukur sebagai sumber utama. Tradisi bercukur di dunia Melayu tidak hanya berfungsi sebagai praktik sosial, tetapi juga mengandung nilai-nilai spiritual yang memperkuat hubungan antara ajaran Islam dan adat setempat. Melalui pendekatan kuantitatif-kualitatif, penelitian ini menguji beberapa variabel independen, yaitu paparan terhadap Hikayat Nabi Bercukur, intensitas partisipasi dalam ritual bercukur, dan norma keluarga serta tradisi lokal, terhadap variabel dependen berupa identitas keagamaan masyarakat. Hasil penelitian menunjukkan bahwa tingkat paparan terhadap hikayat dan intensitas keterlibatan dalam ritual bercukur memiliki pengaruh signifikan terhadap penguatan identitas keagamaan individu dan komunitas. Sementara itu, norma keluarga dan tradisi kultural berperan sebagai faktor penguat dalam mempertahankan kontinuitas praktik tersebut di tengah modernisasi dan perubahan sosial. Temuan ini menegaskan bahwa tradisi bercukur bukan sekadar warisan budaya, melainkan juga representasi sinkretik antara nilai-nilai Islam dan identitas etno-religius masyarakat Melayu di kepulauan Nusantara. Kata Kunci: Hikayat nabi bercukur; tradisi bercukur; Masyarakat Melayu; Identitas keagamaan; Sinkretisme budaya.